IMPLEMENTASI PENDIDIKAN POLITIK UNTUK MEMBANGUN KESADARAN POLITIK PEREMPUAN GENERASI Z DI ERA DIGITAL (Studi Deskriptif Pada Komunitas Partisipasi Aktif Desa Compreng Tahun 2025) - Umi Nurjanah; Cahyono; Rd Sugara Mochamad Haddad (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2026)
This research is motivated by the importance of increasing the political awareness of Generation Z women in the digital era, especially in Compreng Village, which still faces limited formal political education. The research problem formulation includes: (1) how is political education implemented for women in the Z community, (2) factors that influence political awareness, and (3) the role of technology and social media in increasing political participation. The purpose of this research is to analyze the implementation of political education, identify supporting and inhibiting factors, and examine the contribution of digital media to the political awareness of Generation Z women. The research uses the theory of implementation, political education, and Branson's (1998) concept of civic education. The approach used is qualitative with descriptive methods. Data were collected through interviews, observations, and documentation with female Gen Z respondents, village officials, and community leaders. The results show that the implementation of political education mostly takes place non-formally and informally through community forums and digital media. Factors that influence political awareness include education, family environment, community leaders, and access to social media. Digital media has proven to be a primary means of expanding young women's political participation. In conclusion, political education in Compreng Village is still partial, but has great potential to develop if managed in an integrated manner by the village government, educational institutions, communities and the public.